Analysis of Mathematical Problem-Solving Skills Through Solving Fraction Problems in 3rd Grade Students of SDN 4 Karangmalang - Amalia, Fitriyah; Hanafi, Taufiq; Lestari, Erlanda Dinda; Sofiyani; Putri, Aurelia Theysa (MultiTech Publisher, 2023)
This study aims to describe the mathematical solving of grade 3 elementary school fractions as a form of education. Education is the acquisition of knowledge, skills, and habits by a group of people, which are transmitted from one generation to the next through teaching, training or research. The research method used in this article is a descriptive research method with a qualitative approach. Sources of data come from scores of written test results and problem-solving abilities, documents, and interviews. The research instrument used was test questions to obtain data on students' mathematical problem-solving abilities. Data collection techniques carried out by researchers were written tests, documentation, and interviews. Based on the results of the study it was concluded that the results of this analysis can be a reference for teachers and schools to identify areas of student weakness and design appropriate learning strategies to improve their mathematical problem-solving abilities.